Effect of a Histone Demethylase Inhibitor on Equine Herpesvirus-1 Activity In Vitro - Tallmadge, Rebecca L.; Žygelytė, Emilija; Van de Walle, Gerlinde R.; Kristie, Thomas M.; Felippe, M. Julia B. (Frontiers in Veterinary Science, 2018)
Equine herpesvirus type-1 (EHV-1) is a ubiquitous and highly contagious pathogen that causes a range of disease severities with outbreaks of notable economic impact. Given the limitations in immune protection of current vaccines and the limited effectiveness of antiviral drugs on EHV-1 infections in vivo, improved treatment measures are needed to control disease. The use of drugs that alter the epigenetic state of herpes simplex virus (HSV) genome has been shown to limit viral primary infection and reactivation both in vitro and in vivo. Therefore, we tested the hypothesis that maintaining a repressive epigenetic state on the EHV-1 genome in the host equine cell would decrease viral load during lytic infection. Equine fetal kidney cells (EFKCs) or isolated peripheral blood leukocytes were treated in vitro with a) the nucleoside analogue ganciclovir; b) the histone demethylase inhibitor OG-L002; c) both ganciclovir and OG-L002; or d) dimethyl sulfoxide (DMSO, vehicle control); and then infected with a clinical EHV-1 isolate. Treatment of EFKCs with ganciclovir (mean 22.3 DNA copies per cell, p=0.0005), OG-L002 (mean 25.6, p=0.005) or both ganciclovir and OG-L002 (mean 7.1, p=0.0001) resulted in decreased EHV-1 viral load at 24 hours post-infection (hpi) in comparison with DMSO (mean 42.0), with greater impact using the combined treatment. Further, EHV-1 gene expression at 3 hpi decreased when EFKCs were infected in the presence of ganciclovir (p=0.04), and combined treatment of ganciclovir and OG-L002 (p=0.0003). In contrast, under similar conditions, neither ganciclovir nor OG-L002 suppressed EHV-1 infection in leukocytes. Differences between cell types, drug penetrance, or drug turnover, may have contributed to the distinct effects observed in this study.